Demersal fishes and their distribution in estuarine waters of Mahakam Delta, East Kalimantan - IWAN SUYATNA; ACHMAD ARIFFIEN BRATAWINATA; ACHMAD SYAFEI SIDIK; AFIF RUCHAEMI (Society for Indonesian Biodiversity, 2010)
Suyatna I, Bratawinata AA, SidikAS, Ruchaemi A (2011) Demersal fishes and their distribution in estuarine waters of Mahakam Delta, East Kalimantan. Biodiversitas 12: 204-210. The study aimed (i) to identify of the demersal fishes, (ii) to analyze the diversity and (iii) to determine their distribution. Surveys were carried out between August 2009 and January 2010 in Mahakam Delta, East Kalimantan. Data were analyzed using several indices of Shannon Weaver, Simpson, Margalef species richness, and Bray Curtis distance. The canonical correspondence analysis (CCA) was also used to correlate between fish species and their environmental factors and to show the fish distribution. Sixty samplings were done using bottom-trawl at various water depths from one to forty two meters to collect the data. Taxonomically, during the study, 10 orders, 61 families, 87 genera and 131 species of fish with 43340 individuals were identified. Among the families, Leiognathidae was the most important group of fish, they distributed throughout the depths. Meanwhile CCA showed that Leiognathidae and Sciaenidae were observed to be rich in the shallow water. Generally, index of Shannon Weaver, Simpson and Margalef species richness ranged between; 0.52 and 2.48; 0.11 and 0.82; 2.24 and 18.61 respectively. Bray Curtis distanceindicated the significant difference of individual number of demersal fishes between shallow and deep waters.Key words: Mahakam delta, water depth, trawl, demersal fish, canonical correspondence analysis